2014
DOI: 10.5798/diclemedj.0921.2014.01.0380
|View full text |Cite
|
Sign up to set email alerts
|

Our experiences on retrograde intrarenal surgery

Abstract: Objective: To evaluate outcomes of the cases who had undergone retrograde intrarenal surgery (RIRS) in our clinics. Methods:Outcomes of 100 cases who had undergone RIRS because of renal stones between February 2012, and May 2013 were retrospectively evaluated.Results: Study population consisted of 35 female and 65 male patients with a mean age of 36.81(1-76) years. RIRS was performed with the indication of rest double J (D-J) stent (n=1), and renal stone (n=99). Mean stone size was 15.26 (5-27) mm. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…duration of fluoroscopy and operation were significantly shorter compared to the control group (p < 0.001, p = 0.036 respectively). In two different recent studies about the use of ureteral access sheath, the fluoroscopy time was measured as 39 and 52.72 sec (18,19). This figures demonstrates that the Endovisional technique significantly shortens fluoroscopy time.…”
Section: Discussionmentioning
confidence: 86%
“…duration of fluoroscopy and operation were significantly shorter compared to the control group (p < 0.001, p = 0.036 respectively). In two different recent studies about the use of ureteral access sheath, the fluoroscopy time was measured as 39 and 52.72 sec (18,19). This figures demonstrates that the Endovisional technique significantly shortens fluoroscopy time.…”
Section: Discussionmentioning
confidence: 86%
“…In their study, Hatipoğlu et al applied RIRC to patients with a mean stone size of 15.26 mm and reported a stone-free rate of 87%. The authors found that this rate increased to 91% after the second RIRC (9). Reşorlu et al examined the factors affecting success RIRC in their study with 207 patients and reported that stone size significantly affected the success rate (10).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Besides, RIRS is the standard treatment method in a group of patients having some special conditions such as anticoagulant use, obesity, musculoskeletal deformity, concomitant ureteropelvic stenosis, ESWL-resistant stones, and renal anomalies. 16 The 2016 European Association of Urology guidelines on urolithiasis state, "Most interventions are performed under GA, although local or spinal anesthesia is possible." This was a big challenge as no specific indications on the gold standard have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Besides, RIRS is the standard treatment method in a group of patients having some special conditions such as anticoagulant use, obesity, musculoskeletal deformity, concomitant ureteropelvic stenosis, ESWL-resistant stones, and renal anomalies. 16…”
Section: Discussionmentioning
confidence: 99%